Plastynacja – sztuka, piękno, prowokacja, patologia? - Guzik-Makaruk, Ewa (Studia Prawnoustrojowe, 2019)
This text is about so called plastination and is divided into seven parts: introduction, defnition, idea and goal of plastination, technique of plastination, exhibitions of plastinates, body donation after death in goal of exhibitions, plastination – art, beauty, provocation, pathology and resume. Plastination is a technique or process used in anatomy to preserve bodies or body parts, frst developed by Günther von Hagens in 1977. The water and fat are replaced by certain plastics, yielding specimens that can be touched, do not smell or decay, and even retain most properties of the original sample.